2017
DOI: 10.3389/fnagi.2017.00168
|View full text |Cite
|
Sign up to set email alerts
|

Neuroprotective and Anti-Aging Potentials of Essential Oils from Aromatic and Medicinal Plants

Abstract: The use of essential oils (EOs) and their components is known since long in traditional medicine and aromatherapy for the management of various diseases, and is further increased in the recent times. The neuroprotective and anti-aging potentials of EOs and their possible mechanism of actions were evaluated by numerous researchers around the globe. Several clinically important EOs and their components from Nigella sativa, Acorus gramineus, Lavandula angustifolia, Eucalyptus globulus, Mentha piperita, Rosmarinus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
133
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 214 publications
(154 citation statements)
references
References 104 publications
(111 reference statements)
0
133
0
Order By: Relevance
“…The activities of cholinesterases are important in neurotransmission regulation by the hydrolysis of acetylcholine into choline and acetate (Martorana, Esposito, & Koch, 2010). In the brain of an Alzheimer’s disease patient, the level of cholinesterase activity is increased, this leads the drastic decrease in acetylcholine in the brain leading to a loss of memory, inadequacy in cholinergic neurotransmission and cognitive abilities (Ayaz, Sadiq et al, ; Oboh et al, ). Some studies have shown that in Alzheimer’s disease there is an increase BChE activity.…”
Section: Discussionmentioning
confidence: 99%
“…The activities of cholinesterases are important in neurotransmission regulation by the hydrolysis of acetylcholine into choline and acetate (Martorana, Esposito, & Koch, 2010). In the brain of an Alzheimer’s disease patient, the level of cholinesterase activity is increased, this leads the drastic decrease in acetylcholine in the brain leading to a loss of memory, inadequacy in cholinergic neurotransmission and cognitive abilities (Ayaz, Sadiq et al, ; Oboh et al, ). Some studies have shown that in Alzheimer’s disease there is an increase BChE activity.…”
Section: Discussionmentioning
confidence: 99%
“…It is a general belief that the pleasant aroma of the Jasminum sambac flower can relieve the mood of depression [1]. Moreover, the health effect of tea also has been widely confirmed [2].…”
Section: Introductionmentioning
confidence: 99%
“…These oils are frequently isolated via steam distillation, hydrodistillation, and cold pressing methods [8]. They are administered via inhalation, massage, compress, and rarely, they are taken internally through gelatin capsules, honey water, vaginal pessaries, and suppositories [9].…”
mentioning
confidence: 99%